A Novel β0-Thalassemia Mutation, HBB: c.356_357delTT [Codon 118 (–TT)] in an Iraqi Kurd. (4th May 2021) - Atroshi, Sulav D.; Al-Allawi, Nasir; Chui, David H.K.; Najmabadi, Hossein; Khailany, Rozhgar A.
Abstract: We report a novel frameshift β-thalassemia (β-thal) mutation due to a two-nucleotide deletion at codon 118 of the β-globin gene ( HBB : c.356_357delTT) in a 4-year-old Iraqi Kurd female presenting as transfusion-dependent β-thal. This frameshift mutation, unlike many others involving the third exon, behaved as a recessive β 0 defect and not as dominant β-thal mutation.